PEMBUATAN ANALOG DESIGN DAN LAYOUT IC (INTEGRATED CIRCUIT) AMPLIFER KELAS A - Effendy, Machmud (Jurnal Gamma, 2009)
The making of VLSI design ( Very Large Scale Integrated Scale Integration ) needed byplanning of Analog Design and Layout. Where function of making of Analog Design is to translatethe electric circuit becoming a verilog file which there are information about size of IC (integratedcircuit) tha will be formed to use DSCH. While layout represent pattern form to be used in makingof IC, where pattern form to be made have to pursuant to Analog Design which have been made andpursuant to power amplification value and its efficiency. The making of layout used MICROWINDsoftware. Then its result will in test use program of winspice, so that characteristic of class A amplifiercircuit can be seen graphly.In this research is made analog design and layout for the circuit of amplifier class A, thismatter is caused by this circuit still is often used in audio technology and radio, amplifier circuit ofclass A in the form of IC still seldom in selling marketing, and the last amplifier circuit of class Anot to integrated to require compared to higher level energy dissipation which have integrated.